Curriculum-Based Empowerment through Local Knowledge Integration in Vocational Schools - Hariyanti, Titik (Chatra: Jurnal Pendidikan dan Pengajaran, 2025)
The integration of local wisdom into vocational school curricula is a strategic approach to enhancing the relevance of education within specific social and cultural contexts. This study aims to explore the strategies for incorporating local wisdom into the curriculum at SMK Negeri 2 Sangatta Utara and its impact on student empowerment and graduate competitiveness. A descriptive qualitative approach was employed using a case study design. Data were collected through in-depth interviews, participant observation, documentation, focus group discussions, and tracer studies. Participants included teachers, school administrators, students, alumni, and local stakeholders. Data analysis was conducted thematically through data reduction, display, and conclusion drawing. The results indicate that local wisdom is integrated through contextual learning, community collaboration, and the internalization of cultural values in vocational practices. Supporting factors such as school commitment and community engagement strengthen the implementation process. These findings underscore the importance of a locally grounded approach in vocational education to produce adaptive, character-driven graduates capable of responding to global challenges. This study contributes to the development of inclusive and context-sensitive curricula, promoting sustainable educational innovation.